(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the effectiveness of Total Physical Response (TPR) as a teaching approach in English language instruction for young learners. TPR is a language teaching method that integrates physical movement with langinteractive activities. The study examines the theoretical foundations of TPR, its practical application in the classroom, and its impact on vocabulary retention, listening comprehension, and learner engagement. Through a review of existing literature and practical examples, this article highlights the advantages of using TPR in creating a dynamic, fun, and effective language learning environment for young learners. The findings suggest that TPR not only enhances language acquisition but also fosters a positive learning experience, making it an essential strategy for educators working with young English language learners.